Positive electrode active material and preparation method thereof, positive electrode plate, secondary battery and electric device
Patent Information
- Application Number
- CN202380066573.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-18
- Publication Date
- 2025-04-25
AI Technical Summary
The existing nickel-containing positive electrode material secondary batteries with high nickel content have problems with low efficiency and poor high temperature performance for the first time. Especially, there is a high content of low-active residual lithium and rock salt layer on the surface of the particles of high nickel positive electrode material, resulting in lithium ions retracting. It is blocked and negatively reacts with the electrolyte at high temperature.
Using lithium-containing nickel-based transition metal oxides as the core, and covering the surface with cerium elements and other materials to form a dense cladding layer, improving the transmission rate of lithium ions and the high-temperature performance of the battery, activates the lithiated rock salt structure through cerium elements, and reduces the DC internal resistance and reduce active site erosion through the second cladding layer.
It improves the first Coulomb efficiency and high-temperature circulation performance of secondary batteries, enhances high-temperature storage performance, and reduces DC internal resistance and high-temperature gas production.
Smart Images

Figure CN119895589A_ABST
Abstract
Description
Positive electrode active material and preparation method thereof, positive electrode sheet, secondary battery and electrical device Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] Secondary batteries are widely used in various consumer electronics and electric vehicles due to their outstanding features such as light weight, pollution-free, and no memory effect. Moreover, as people's awareness of green travel and low-carbon living continues to strengthen, the market demand for secondary batteries is growing, and their application range is becoming wider and wider. The positive electrode material is a key component of secondary ion batteries. As an electrode material, it participates in the electrochemical reaction of the battery and also acts as a lithium ion source during the operation of the battery. In related technologies, in order to increase the energy density of the battery, nickel-containing positive electrode materials are often used.
[0003] However, secondary batteries using nickel-containing positive electrode materials with high nickel content as positive electrode active materials generally have problems such as low first coulombic efficiency and poor high-temperature performance.
[0004] Summary of the Invention
[0005] In view of the technical problems existing in the background technology, the present application provides a positive electrode active material and a preparation method thereof, a positive electrode plate, a secondary battery and an electrical device, aiming to improve the first coulombic efficiency and high-temperature performance of the secondary battery.
[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode active material, comprising:
[0007] A core, the core comprising a lithium-containing nickel-based transition metal oxide; in the lithium-containing nickel-based transition metal oxide, the molar proportion of nickel in the total elements other than lithium and oxygen is 50% to 100%;
[0008] A first coating layer is coated on at least a portion of the outer surface of the core, and the first coating layer includes cerium.
[0009] Compared with the prior art, this application has at least the following beneficial effects:
[0010] The positive electrode active material of the present application has a first coating layer coated on at least a portion of the outer surface of its core, the coating layer including cerium. During the preparation of the positive electrode active material, the cerium does not affect the active lithium content on the core surface. At the same time, the cerium activates the lithiated rock salt structure on the core surface, thereby making the lithium in the lithiated rock salt structure more active, thereby improving the initial coulombic efficiency of the secondary battery. Furthermore, when a cerium-containing oxide is used as a cerium-containing precursor, the cerium-containing oxide reacts with the residual lithium on the core surface to form LiCeO2 with high ionic conductivity, thereby increasing the lithium ion transfer rate on the core surface and reducing the DC internal resistance of the secondary battery. Furthermore, the cerium-containing oxide easily forms a dense coating layer on the core surface, which can improve the high-temperature cycling performance and high-temperature storage performance of the secondary battery while reducing the erosion of the core's active sites by electrolyte byproducts.
[0011] In any embodiment of the present application, the first coating layer further includes one or more of cobalt and fluorine.
[0012] In any embodiment of the present application, the first coating layer has at least one of the following characteristics:
[0013] (1) The sum of the mass of the cerium element and the cobalt element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 100 ppm to 20,000 ppm; optionally, 1,000 ppm to 15,000 ppm;
[0014] Optionally, the molar ratio of the cobalt element to the cerium element is (0-0.5):1;
[0015] (2) The mass of the fluorine element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 0 ppm-60,000 ppm; optionally 300 ppm-60,000 ppm; further optionally 3,000 ppm-45,000 ppm.
[0016] In any embodiment of the present application, the chemical formula of the lithium-containing nickel-based transition metal oxide is LiNi x Co y Mn z M a M / b O2, wherein the M element includes one or more of Zr, Y, Al, Ti, W, Sr, Ta, Mo, Sb, Nb, Na, K and Ca, M / The elements include one or more of N, F, S and Cl, 0.6≤x≤1, and x+y+z+a+b=1.
[0017] In any embodiment of the present application, 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2, and 0≤a≤0.1.
[0018] In any embodiment of the present application, the positive electrode activation material further includes a second coating layer coated on at least a portion of the outer surface of the first coating layer, and the second coating layer includes one or more of aluminum and boron.
[0019] In any embodiment of the present application, the second coating layer comprises the aluminum element and the boron element in a mass ratio of (0.5-2):1;
[0020] Optionally, the mass content of the aluminum element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 100ppm-3500ppm; further optionally, 500ppm-2500ppm;
[0021] Optionally, the mass of the boron element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 100ppm-2500ppm; further optionally, it is 500ppm-2000ppm.
[0022] In any embodiment of the present application, the sum of the thicknesses of the first coating layer and the second coating layer is 0.01 μm-1 μm.
[0023] In any embodiment of the present application, the volume average particle size Dv90 of the positive electrode active material is denoted as d 90 The volume average particle size Dv50 of the positive electrode active material is recorded as d 50 The volume average particle size Dv10 of the positive electrode active material is recorded as d 10 The volume average particle size Dv90, volume average particle size Dv50 and volume average particle size Dv10 of the positive electrode active material satisfy the following requirements: (d 90 -d 10 ) / d 50 ≥0.5; optional (d 90 -d 10 ) / d 50 ≥1.2.
[0024] In any embodiment of the present application, the residual lithium content of the positive electrode active material is recorded as Rsd(Li), and the residual lithium content of the positive electrode active material satisfies: 0.15wt%≤Rsd(Li)≤0.35wt%; optionally 0.18wt%≤Rsd(Li)≤0.24wt%.
[0025] In any embodiment of the present application, the oxygen deficiency index of the positive electrode active material is marked as ODI, and the oxygen deficiency index of the positive electrode active material satisfies: ODI≥1.75; optionally ODI≥1.8.
[0026] The second aspect of the present application provides a method for preparing the positive electrode active material of the first aspect of the present application, comprising the following steps:
[0027] Mixing a lithium salt, a nickel-containing material precursor, and optional additives, and performing a first sintering process to prepare the core;
[0028] The core, a precursor containing cerium, an optional precursor containing cobalt, and an optional precursor containing fluorine are mixed, and subjected to a second sintering treatment to prepare the first coating layer on the outer surface of the core;
[0029] Wherein, the elements contained in the optional additives include M element and M / One or more of the elements; the M element includes one or more of Zr, Y, Al, Ti, W, Sr, Ta, Mo, Sb, Nb, Na, K and Ca, the M / The elements include one or more of N, F, S and Cl.
[0030] In any embodiment of the present application, the molar amount of the lithium element contained in the lithium salt is recorded as m1, the molar amount of the nickel element, cobalt element, manganese element contained in the nickel-containing material precursor and the M element and M contained in the optional additive are recorded as m2. / The sum of the molar amounts of the elements is recorded as m2, and the ratio of m1 to m2 is (0.9-1.1):1.
[0031] In any embodiment of the present application, the lithium salt includes one or more of lithium hydroxide, lithium carbonate, lithium acetate, lithium nitrate, lithium oxalate and lithium sulfate;
[0032] The optional additives include oxides, hydroxides, acids, fluorides, chlorides, sulfates, nitrates, oxalates, acetates, carbonates, lithium salts, ammonium salts, sodium salts of the M element, and / One or more of the ammonium salts of the elements;
[0033] Optionally, the optional additives include one or more of zirconium oxide, zirconium fluoride, zirconium chloride, yttrium oxide, yttrium sulfate, yttrium nitrate, yttrium oxalate, yttrium acetate, yttrium chloride, aluminum oxide, aluminum fluoride, aluminum chloride, lithium aluminate, titanium oxide, lithium titanate, tungsten oxide, tungstic acid, ammonium tungstate, sodium tungstate, lithium tungstate, strontium oxide, tantalum oxide, niobium oxide, lithium niobate, molybdenum oxide, lithium molybdate, antimony oxide, lithium antimonate, sodium hydroxide, sodium carbonate, sodium chloride, sodium fluoride, sodium oxide, potassium hydroxide, potassium carbonate, potassium chloride, potassium oxide, calcium hydroxide, calcium carbonate, calcium oxide, calcium chloride, calcium fluoride and ammonium chloride;
[0034] The cerium-containing precursor includes one or more of cerium oxide, cerium fluoride, cerium chloride, cerium sulfide, cerium nitrate and cerium hydroxide;
[0035] The optional fluorine-containing precursor includes one or more of cerium fluoride and ammonium fluoride;
[0036] The optional cobalt-containing precursor includes one or more of cobalt trioxide, cobalt hydroxide, cobaltous oxide, cobalt oxyhydroxide, cobalt acetate, cobalt oxalate and cobalt carbonate.
[0037] In any embodiment of the present application, the first sintering process includes at least one of the following conditions:
[0038] (1) Sintering temperature is 700℃-900℃;
[0039] (2) Sintering time is 10h-20h;
[0040] (3) The sintering atmosphere is selected from one of air and oxygen;
[0041] The second sintering process includes at least one of the following conditions:
[0042] (1) Sintering temperature is 300℃-650℃;
[0043] (2) Sintering time is 3h-10h;
[0044] (3) The sintering atmosphere is selected from one of air and oxygen.
[0045] In any embodiment of the present application, the method further comprises the following steps:
[0046] After the first coating layer is prepared on the surface of the core, it is mixed with a precursor containing aluminum and a precursor containing boron, and subjected to a third sintering treatment to coat the outer surface of the first coating layer with the second coating layer.
[0047] In any embodiment of the present application, the precursor containing aluminum element includes one or more of aluminum oxide, aluminum hydroxide, aluminum sulfate, aluminum chloride and aluminum nitrate;
[0048] The boron-containing precursor includes one or more of boron chloride, boron sulfate, boron nitrate, boron nitride, boron oxide, boron fluoride, boron bromide, boron iodide, boric acid, H2BO5PC5H6B(OH)2, C3H9B3O6, (C2H5O)3B and (C3H7O)3B.
[0049] In any embodiment of the present application, the third sintering treatment includes at least one of the following conditions:
[0050] (1) The sintering temperature is 200℃-500℃;
[0051] (2) Sintering time is 5h-15h;
[0052] (3) The sintering atmosphere is selected from one of air and oxygen.
[0053] The third aspect of the present application provides a positive electrode plate, comprising:
[0054] positive electrode current collector;
[0055] The positive electrode active material layer is located on at least one side of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared by the method of the second aspect of the present application.
[0056] The fourth aspect of the present application provides a secondary battery, comprising the positive electrode sheet of the third aspect of the present application.
[0057] A fifth aspect of the present application provides an electrical device comprising the secondary battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.
[0059] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application.
[0060] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 1 .
[0061] FIG3 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0062] Description of reference numerals: 1 secondary battery; 11 housing; 12 electrode assembly; 13 cover plate; 2 power-consuming device. DETAILED DESCRIPTION
[0063] The present application will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0064] For the sake of clarity, only some numerical ranges are specifically disclosed herein. However, any lower limit may be combined with any upper limit to form an unspecified range; and any lower limit may be combined with other lower limits to form an unspecified range, and similarly, any upper limit may be combined with any other upper limit to form an unspecified range. In addition, each individually disclosed point or single value may itself serve as a lower limit or upper limit and be combined with any other point or single value, or with other lower limits or upper limits, to form an unspecified range.
[0065] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0066] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0067] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0068] In this description, terms such as "first aspect," "second aspect," and "third aspect" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor as implicitly indicating the importance or quantity of the technical features indicated. Furthermore, terms such as "first," "second," and "third" serve only as non-exhaustive enumerations and should not constitute closed-ended limitations on quantity.
[0069] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0070] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0071] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” include the number itself, and “several” in “one or several” means two or more.
[0072] In the description herein, unless otherwise stated, the term "or" is inclusive. That is, the phrase "A or (or) B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist). Unless otherwise stated, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise stated, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0073] At present, secondary batteries that use nickel-containing positive electrode materials with high nickel content as positive electrode active materials have the problem of low first coulombic efficiency; in addition, the first discharge capacity of the secondary battery is low and the high-temperature performance is poor. In particular, when the nickel content in the nickel-containing positive electrode material is higher, although the energy density of the secondary battery can be significantly improved, the problems of low first coulombic efficiency, low first discharge capacity, and poor high-temperature storage and cycle performance of the secondary battery are more obvious. The technical personnel of this application analyzed and found that the main problems are: there is a high content of low-activity residual lithium, rock salt layer and cation mixing on the surface of the high-nickel positive electrode material particles, so the lithium ion back-intercalation will be greatly hindered, resulting in low first coulombic efficiency and first discharge capacity of the secondary battery; at the same time, in the state of large-scale delithiation, there is highly active lattice oxygen on the surface of the high-nickel positive electrode material particles, which is easy to react negatively with the electrolyte, thereby resulting in poor high-temperature performance of the secondary battery.
[0074] The first aspect of the present application provides a positive electrode active material, comprising: a core and a first coating layer coated on at least a portion of the outer surface of the core; the core comprises a lithium-containing nickel-based transition metal oxide, and the first coating layer comprises a cerium element; in the lithium-containing nickel-based transition metal oxide, the molar proportion of nickel in the total elements other than lithium and oxygen is 50%-100%.
[0075] It should be noted that the term "first coating layer" is used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor as implicitly indicating the importance or quantity of the indicated technical features. The first coating layer may cover a portion of the outer surface of the core or the entire outer surface of the core; preferably, the first coating layer covers the entire outer surface of the core.
[0076] The lithium-containing nickel-based transition metal oxide mentioned above contains both lithium and nickel elements. The lithium-containing nickel-based transition metal oxide may be undoped with other elements or may be doped with other elements; for example, it may be doped with one or more metal elements and non-metal elements, which can be selected according to actual needs.
[0077] In the lithium-containing nickel-based transition metal oxide mentioned above, the molar proportion of nickel in the total elements other than potassium and oxygen is 50%-100%; for example, it can be 55%-100%, 55%-95%, 60%-90%, 65%-85%, 70%-80% or 75%-80%, etc., without specific limitation. When the molar proportion of nickel in the total elements other than potassium and oxygen in the lithium-containing nickel-based transition metal oxide is within the above range, using it as the core of the positive electrode active material can increase the gram capacity of the positive electrode active material and improve the energy density of the secondary battery. As an example, in the lithium-containing nickel-based transition metal oxide, the molar proportion of nickel in the total elements other than potassium and oxygen can be, but is not limited to, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or a range between any two of the above values, without specific limitation.
[0078] It should be noted that the elements other than potassium and oxygen mentioned above generally refer to all other elements contained in the lithium-containing nickel-based transition metal oxide except potassium and oxygen.
[0079] As an example, in the above-mentioned lithium-containing nickel-based transition metal oxide, the molar proportion of nickel in the total elements other than potassium and oxygen can be determined with reference to EPA 6010D-2014 standard, specifically: using ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing, the sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization, and the gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then recovered from the excited state to the ground state; in the above process, energy is released and recorded as different characteristic spectral lines, and element trace analysis is performed based on the characteristic spectral lines to obtain the molar proportion of nickel in the total elements other than potassium and oxygen in the lithium-containing nickel-based transition metal oxide.
[0080] It is understood that the above-mentioned positive electrode active material has a first coating layer coated on at least part of the outer surface of its core, and the coating layer includes cerium. During the preparation of the positive electrode active material, the cerium element does not affect the active lithium content on the core surface. At the same time, the cerium element can activate the lithiated rock salt structure on the core surface, thereby making the lithium in the lithiated rock salt structure more active, thereby improving the first coulombic efficiency of the secondary battery. In addition, when a cerium-containing oxide is used as a cerium-containing precursor, the cerium-containing oxide can react with the residual lithium on the core surface to form LiCeO2 with high ionic conductivity, thereby increasing the transfer rate of lithium ions on the core surface and reducing the DC internal resistance of the secondary battery. At the same time, the cerium-containing oxide easily forms a dense coating layer on the core surface, which can improve the high-temperature cycle performance and high-temperature storage performance of the secondary battery on the basis of reducing the corrosion of the active sites of the core by electrolyte byproducts.
[0081] In some embodiments, the first coating layer further includes one or more of cobalt and fluorine. When cobalt is included in the first coating layer, it does not affect the active lithium content on the surface of the inner core during the preparation of the positive electrode active material. Furthermore, when a cerium-containing oxide is used as a cerium-containing precursor, the cerium-containing oxide readily forms a dense coating on the inner core surface, reducing the erosion of the inner core's active sites by electrolyte byproducts, thereby improving the high-temperature cycling and storage performance of the secondary battery. Fluorine can suppress the formation of oxygen vacancies.
[0082] In some embodiments, the sum of the mass of the cerium and cobalt elements in the first coating layer relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 100ppm-20000ppm; for example, it can be 1000ppm-19000ppm, 2000ppm-18000ppm, 3000ppm-17000ppm, 4000ppm-16000ppm, 5000ppm-15000ppm, 6000ppm-14000ppm, 7000ppm-13000ppm, 8000ppm-12000ppm or 9000ppm-11000ppm, etc., without specific limitation. When the sum of the mass of the cerium and cobalt elements relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is within the above range, a uniform coating layer can be formed on the surface of the core, and the reduction in specific capacity caused by the formation of island-like accumulation of elements on the surface of the core can also be reduced or even avoided. As an example, the sum of the mass of the cerium element and the cobalt element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core can be, but is not limited to, 100 ppm, 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, 8000 ppm, 9000 ppm, 10000 ppm, 11000 ppm, 12000 ppm, 13000 ppm, 14000 ppm, 15000 ppm, 16000 ppm, 17000 ppm, 18000 ppm, 19000 ppm, 20000 ppm, or a range between any two of the above values. Alternatively, the sum of the mass of the cerium element and the cobalt element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 1000 ppm-15000 ppm.
[0083] In some embodiments, in the first coating layer, the molar ratio of cobalt to cerium is (0-0.5):1; for example, it can be (0.05-0.5):1, (0.1-0.5):1, (0.15-0.5):1, (0.2-0.5):1, (0.25-0.5):1, (0.3-0.5):1, (0.35-0.5):1, (0.4-0.5):1 or (0.45-0.5):1, etc., and is not specifically limited. When the molar ratio of cobalt to cerium is within the above range, the secondary battery can have a low DC internal resistance, as well as excellent gram capacity, first coulombic efficiency, high temperature storage performance and high temperature cycle performance, and can reduce the high temperature gas production of the secondary battery. As an example, the molar ratio of cobalt to cerium can be, but is not limited to, 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or a range between any two of the above values.
[0084] In some possible embodiments, in the first coating layer, the mass content of fluorine element relative to the mass content of lithium-containing nickel-based transition metal oxide in the core is 0ppm-60000ppm; for example, it can be but not limited to 0ppm, 300ppm, 500ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm, 11000ppm, 12000ppm, 13000ppm, 14000ppm, 15000ppm, 16000ppm, 17000ppm, 18000ppm, 19000ppm, 20000ppm, 21000ppm, 22000ppm, 23000ppm, 24000ppm, 25000ppm, 26000ppm, 27000ppm, 28000ppm, 29000ppm, 30000ppm, 31000ppm, 32000ppm, 33000ppm, 34000ppm, 35000ppm, 36000ppm, 37000ppm, 38000ppm, 39000ppm, 4000ppm, 41000ppm, 42000ppm, 43000ppm, 44000ppm, 45000ppm, 46000ppm, 47000ppm, 48000ppm, 49000ppm, 5000ppm, 51000ppm, 51000ppm, 51000ppm, 51000ppm, 51000ppm, 51000ppm 000ppm, 23000ppm, 24000ppm, 25000ppm, 26000ppm, 27000ppm, 28000ppm, 29000ppm, 30000ppm, 41000ppm, 42000ppm, 43000ppm, 44000ppm, 45000ppm, 46000ppm, 47000ppm, 48000ppm, 49000ppm, 50000ppm, 51000ppm, 52000ppm, 53000ppm, 54000ppm, 55000ppm, 56000ppm, 57000ppm, 58000ppm, 59000ppm, 60000ppm or the range between any two of the above values. When the mass content of the fluorine element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is within the above range, a uniform coating layer can be formed on the surface of the core, while also reducing or even avoiding the problem of increased nickel valence due to excessive fluorine, thereby affecting the performance of gram capacity. Optionally, the mass content of the fluorine element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 300ppm-60000ppm. Further optionally, the mass content of the fluorine element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 3000ppm-45000ppm.
[0085] As an example, in the first coating layer mentioned above, the sum of the masses of cerium and cobalt elements relative to the mass content of the lithium-nickel-based transition metal oxide in the core, and the molar ratio of cobalt and cerium elements can be determined with reference to the EPA 6010D-2014 standard. Specifically: ICP-OES (elemental analysis-inductively coupled plasma emission spectrometry) testing can be used, and the sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then recovered to the ground state from the excited state; in the above process, energy is released and recorded as different characteristic spectral lines, and element trace analysis is performed based on the characteristic spectral lines to determine the form of the Co and Ce elements, and the above results are calculated.
[0086] As an example, the mass of the fluorine element in the first coating layer mentioned above relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core can be determined by the following method: EDS (Energy Dispersive X-ray Spectrometer) can be used for qualitative or semi-quantitative analysis, that is, the sample surface is bombarded with an electron beam in a vacuum chamber to excite the substance to emit characteristic x-rays, and the fluorine element is qualitatively and semi-quantitatively analyzed according to the wavelength of the characteristic x-rays.
[0087] In some embodiments, the chemical formula of the lithium-containing nickel-based transition metal oxide is LiNi x Co y Mn z M a M / b O2, wherein the M element includes one or more of Zr, Y, Al, Ti, W, Sr, Ta, Mo, Sb, Nb, Na, K and Ca, M / The element includes one or more of N, F, S and Cl, 0.6≤x≤1, x+y+z+a+b=1. Optionally, 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2, 0≤a≤0.1.
[0088] As an example, the chemical formula of the lithium nickel-based transition metal oxide mentioned above is LiNi x Co y Mn z M a M / bThe specific values of x, y, z, a, and b in O2 can be measured with reference to the EPA 6010D-2014 standard. Specifically, ICP-OES (elemental analysis - inductively coupled plasma optical emission spectrometry) testing can be used. The sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then return to the ground state from the excited state. In the above process, energy is released and recorded as different characteristic spectral lines, and quantitative elemental analysis is performed based on the characteristic spectral lines.
[0089] In some embodiments, the positive electrode active material further includes a second coating layer coated on at least a portion of the outer surface of the first coating layer, wherein the second coating layer includes one or more of aluminum and boron. The coating of the second coating layer containing aluminum and boron forms a glassy substance of LiAlO2 and Li3BO3, which is well coated at the grain boundaries of the particles, suppressing the generation of oxygen defects and thereby inhibiting gas generation during high-temperature storage.
[0090] It should be noted that the second coating layer is used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor as implicitly indicating the importance or quantity of the indicated technical features. The second coating layer may cover a portion of the outer surface of the first coating layer, or may cover the entire outer surface of the second coating layer; preferably, the second coating layer covers the entire outer surface of the first coating layer.
[0091] The second coating layer may include one of aluminum and boron, or may include both aluminum and boron. Preferably, the second coating layer includes both aluminum and boron.
[0092] As a possible embodiment, the second coating layer includes aluminum and boron in a mass ratio of (0.5-2): 1; for example, the mass ratio of aluminum and boron in the second coating layer can be (0.6-2): 1, (0.6-1.9): 1, (0.7-1.8): 1, (0.8-1.7): 1, (0.9-1.6): 1, (1-1.5): 1, (1.1-1.4): 1 or (1.2-1.3): 1, etc., and is not specifically limited. When the mass ratio of aluminum and boron in the second coating layer is within the above range, the secondary battery can have a lower DC internal resistance, as well as excellent gram capacity, first coulomb efficiency, high temperature storage performance and high temperature cycle performance, while also reducing the high temperature gas production of the secondary battery. As an example, the mass ratio of aluminum element and boron element in the second coating layer can be but is not limited to 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1 or a range between any two of the above values.
[0093] In some embodiments, the mass content of aluminum in the second coating layer relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 100ppm-3500ppm; for example, it can be 100ppm-3300ppm, 300ppm-3000ppm, 500ppm-2700ppm, 800ppm-2500ppm, 1000ppm-2300ppm, 1300ppm-2000ppm, or 1500ppm-1800ppm, etc., without specific limitation. When the mass content of aluminum relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is within the above range, a uniform second coating layer can be formed on the surface of the first coating layer, and the reduction in specific capacity caused by the formation of island-like accumulation of aluminum on the surface of the first coating layer can also be reduced or even avoided. As an example, the mass content of the aluminum element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core can be, but is not limited to, 100 ppm, 300 ppm, 500 ppm, 800 ppm, 1000 ppm, 1300 ppm, 1500 ppm, 1800 ppm, 2000 ppm, 2300 ppm, 2500 ppm, 2700 ppm, 3000 ppm, 3300 ppm, 3500 ppm, or a range between any two of the foregoing values. Alternatively, the mass content of the aluminum element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 500 ppm-2500 ppm.
[0094] In some embodiments, the mass content of boron in the second coating layer relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 100ppm-2500ppm; for example, it can be 100ppm-2300ppm, 300ppm-2000ppm, 500ppm-1700ppm, 800ppm-1500ppm, or 1000ppm-1300ppm, etc., without specific limitation. When the mass content of boron relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is within the above range, a uniform second coating layer can be formed on the surface of the first coating layer, and the reduction in specific capacity caused by the formation of island-like accumulation of boron on the surface of the first coating layer can also be reduced or even avoided. As an example, the mass content of the boron element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core can be, but is not limited to, 100 ppm, 300 ppm, 500 ppm, 800 ppm, 1000 ppm, 1300 ppm, 1500 ppm, 1700 ppm, 2000 ppm, 2300 ppm, 2500 ppm, or a range between any two of the foregoing values. Alternatively, the mass content of the aluminum element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 500 ppm-2000 ppm.
[0095] As an example, the mass content of the aluminum element mentioned above relative to the mass content of the lithium-nickel-based transition metal oxide in the core, the mass content of the boron element relative to the mass content of the lithium-nickel-based transition metal oxide in the core, and the mass ratio of the aluminum element to the boron element can be determined with reference to the EPA 6010D-2014 standard. Specifically: ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used, and the sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then recovered to the ground state from the excited state; energy is released in the above process and recorded as different characteristic spectral lines, and quantitative element analysis is performed based on the characteristic spectral lines.
[0096] In some embodiments, the sum of the thickness of the first coating layer and the second coating layer is 0.01μm-1μm; for example, it can be 0.05μm-1μm, 0.1μm-0.9μm, 0.2μm-0.8μm, 0.3μm-0.7μm, 0.4μm-0.6μm or 0.5μm-0.6μm, etc., without specific limitation. When the sum of the thickness of the first coating layer and the second coating layer is within the above range, it is conducive to the rapid transmission of lithium ions on the surface of the core, and at the same time, an effective protective layer can be formed on the outer surface of the core. As an example, the sum of the thickness of the first coating layer and the second coating layer can be, but is not limited to, 0.01μm, 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm or a range between any two of the above values.
[0097] As an example, the sum of the thicknesses of the first and second coating layers mentioned above can be measured using the following method: A sample preparation glue and composite cathode material powder are uniformly mixed and then coated onto copper foil to produce a sample, where the powder weight is 5 times that of the sample preparation glue. The sample is then dried at 60°C for 30 minutes. The prepared sample is cut into 6mm x 6mm pieces using scissors, secured to a sample stage, and placed in an ion polisher. The sample edge is aligned parallel to the centerline (X-axis) and positioned 40-60μm along the Y-axis for cutting. After cutting, an energy dispersive spectrometer (EDS) combined with a scanning electron microscope (SEM) is used to select a suitable particle section from the sample. A linear scan of the characteristic element content of the first and second coating layers is performed along the particle diameter. The particle radius is measured as R. The distance from the particle center to the point where the element content of the first coating layer begins to increase compared to the particle core is L1, and the distance from the particle center to the point where the element content of the second coating layer begins to increase compared to the particle core is L2. The total thickness L of the first and second coating layers is (R - L1)μm.
[0098] In some possible embodiments, the volume average particle size Dv90 of the positive electrode active material is denoted as d 90 The volume average particle size Dv50 of the positive electrode active material is recorded as d 50 The volume average particle size Dv10 of the positive electrode active material is recorded as d 10 The volume average particle size Dv90, volume average particle size Dv50 and volume average particle size Dv10 of the positive electrode active material satisfy the following conditions: (d 90 -d 10 ) / d 50 ≥0.5; optional (d 90 -d 10 ) / d 50 ≥1.2.
[0099] It should be noted that Dv90 refers to the particle size corresponding to 90% of the volume distribution, Dv50 refers to the particle size corresponding to 50% of the volume distribution, and Dv10 refers to the particle size corresponding to 10% of the volume distribution. (Dv90-Dv10) / Dv50 represents the volume particle size distribution diameter spacing of the positive electrode active material, and the volume particle size distribution diameter spacing of the positive electrode active material is ≥0.5; optionally, the volume particle size distribution diameter spacing of the positive electrode active material is ≥1.2. When the volume particle size distribution diameter spacing of the positive electrode active material is ≥0.5, using it to prepare the positive electrode plate can achieve a certain degree of plate space filling effect, so that the compaction density of the positive electrode plate is ≥3.4g / cc.
[0100] As an example, the volume average particle size Dv90, volume average particle size Dv50 and volume average particle size Dv10 of the positive electrode active material mentioned above can be conveniently measured by laser diffraction method for particle size distribution according to GB / T 19077-2016 / ISO 13320:2009, using a laser particle size analyzer, such as the Mastersizer 3000E laser particle size analyzer of Malvern Instruments Ltd., UK.
[0101] In some embodiments, the residual lithium content of the positive electrode active material is recorded as Rsd(Li), and the residual lithium content of the positive electrode active material satisfies: 0.15wt%≤Rsd(Li)≤0.35wt%; for example, it can be 0.16wt%≤Rsd(Li)≤0.35wt%, 0.16wt%≤Rsd(Li)≤0.34wt%, 0.17wt%≤Rsd(Li)≤0.33wt%, 0.18wt%≤Rsd(Li≤0.32wt% %, 0.19wt%≤Rsd(Li)≤0.31wt%, 0.2wt%≤Rsd(Li)≤0.3wt%, 0.21wt%≤Rsd(Li)≤0.29wt%, 0.22wt%≤Rsd(Li)≤0.28wt%, 0.23wt%≤Rsd(Li)≤0.27wt%, 0.24wt%≤Rsd(Li)≤0.26wt% or 0.24wt%≤Rsd(Li)≤0.25wt%, etc., without specific limitation. When the residual lithium content of the positive electrode active material is within the above range, the qualified rate of the positive electrode slurry processing performance can be improved, and the active lithium in the positive electrode active material can be prevented from being too low. As an example, the residual lithium content Rsd(Li) of the positive electrode active material may be, but is not limited to, 0.15 wt%, 0.16 wt%, 0.17 wt%, 0.18 wt%, 0.19 wt%, 0.2 wt%, 0.21 wt%, 0.22 wt%, 0.23 wt%, 0.24 wt%, 0.25 wt%, 0.26 wt%, 0.27 wt%, 0.28 wt%, 0.29 wt%, 0.3 wt%, 0.31 wt%, 0.32 wt%, 0.33 wt%, 0.34 wt%, 0.35 wt%, or a range between any two of the foregoing values. Optionally, the residual lithium content of the positive electrode active material satisfies: 0.18 wt%≤Rsd(Li)≤0.24 wt%.
[0102] It should be noted that the residual lithium content of the positive electrode active material mentioned above refers to the residual lithium content of the entire positive electrode active material.
[0103] As an example, the residual lithium content of the positive electrode active material mentioned above can be determined with reference to GB / T 9736-2008 General method for determination of acidity and alkalinity of chemical reagents. Specifically, 10g-30g of the sample powder to be tested is weighed, 100mL of pure water is added, and the mixture is stirred for 30 minutes. After standing for 10 minutes, a certain amount of filtrate is removed after filtration. A 0.05mol / L hydrochloric acid standard solution is selected, and the bubbles in the burette are discharged. The corresponding sensor and program are selected to start the potentiometric titration test. The residual lithium content is calculated based on the reaction potential of carbonate and hydroxide.
[0104] In some embodiments, the oxygen deficiency index of the positive electrode active material is denoted as ODI, and the oxygen deficiency index of the positive electrode active material satisfies: ODI ≥ 1.75. When the oxygen deficiency index of the positive electrode active material is within the above range, the high-temperature cycling performance and high-temperature storage performance of the secondary battery can be improved, and the storage gas generation of the secondary battery can be reduced. Optionally, the oxygen deficiency index of the positive electrode active material satisfies: ODI ≥ 1.8.
[0105] As an example, the oxygen deficiency index of the above-mentioned positive electrode active material can be determined by the following method: slowly scan the 35-50° interval in the XRD spectrum of the sample to be tested (<2° / min), and process the image according to smoothing and filtering to obtain the diffraction peak areas I101 and I012 of the (101) crystal plane and (012) crystal plane, and calculate the oxygen deficiency index by (I101 / I012)^0.5.
[0106] The second aspect of the present application provides a method for preparing the positive electrode active material of the first aspect of the present application, comprising the following steps:
[0107] Mixing a lithium salt, a nickel-containing material precursor, and optional additives, and performing a first sintering process to prepare a core;
[0108] The core, the precursor containing the cerium element, the optional precursor containing the cobalt element, and the optional precursor containing the fluorine element are mixed, and a second sintering treatment is performed to prepare a first coating layer on the outer surface of the core;
[0109] The optional additives include M elements and M / One or more of the elements; M element includes one or more of Zr, Y, Al, Ti, W, Sr, Ta, Mo, Sb, Nb, Na, K and Ca, M / The elements include one or more of N, F, S and Cl.
[0110] It should be noted that the first sintering process and the second sintering process are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0111] It should be noted that the optional additives refer to materials that can be selectively added when preparing the inner core; the optional cobalt-containing precursor refers to materials that can be selectively added when preparing the first coating layer on the outer surface of the inner core; the optional fluorine-containing precursor refers to materials that can be selectively added when preparing the first coating layer on the outer surface of the inner core.
[0112] In some embodiments, the molar amount of lithium contained in the lithium salt is recorded as m1, the molar amount of nickel, cobalt, manganese contained in the nickel-containing material precursor and the M element and M contained in the optional additives are recorded as m2. / The sum of the molar amounts of the elements is denoted as m2, and the ratio of m1 to m2 is (0.9-1.1):1; for example, it can be (0.91-1.09):1, (0.92-1.08):1, (0.93-1.07):1, (0.94-1.06):1, (0.95-1.05):1, (0.96-1.04):1, (0.97-1.03):1, (0.98-1.02):1, or (0.99-1.01):1, etc., without specific limitation. When the ratio of m1 to m2 is within the above range, the gram capacity of the secondary battery can be increased, meeting the needs of new batteries. As an example, the ratio of m1 to m2 can be, but is not limited to, 0.9:1, 0.91:1, 0.92:1, 0.93:1, 0.94:1, 0.95:1, 0.96:1, 0.97:1, 0.98:1, 0.99:1, 1:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1, 1.1:1 or a range between any two of the above values.
[0113] As a possible embodiment, the lithium salt includes one or more of lithium hydroxide, lithium carbonate, lithium acetate, lithium nitrate, lithium oxalate and lithium sulfate;
[0114] The precursor containing cerium element includes one or more of cerium oxide, cerium fluoride, cerium chloride, cerium sulfide, cerium nitrate and cerium hydroxide;
[0115] Optional fluorine-containing precursors include one or more of cerium fluoride and ammonium fluoride;
[0116] Optional cobalt-containing precursors include one or more of cobalt trioxide, cobalt hydroxide, cobaltous oxide, cobalt oxyhydroxide, cobalt acetate, cobalt oxalate and cobalt carbonate.
[0117] Optional additives include oxides, hydroxides, acids, fluorides, chlorides, sulfates, nitrates, oxalates, acetates, carbonates, lithium salts, ammonium salts, sodium salts of the M element, and / One or more ammonium salts of elements.
[0118] In some embodiments, the optional additives include one or more of zirconium oxide, zirconium fluoride, zirconium chloride, yttrium oxide, yttrium sulfate, yttrium nitrate, yttrium oxalate, yttrium acetate, yttrium chloride, aluminum oxide, aluminum fluoride, aluminum chloride, lithium aluminate, titanium oxide, lithium titanate, tungsten oxide, tungstic acid, ammonium tungstate, sodium tungstate, lithium tungstate, strontium oxide, tantalum oxide, niobium oxide, lithium niobate, molybdenum oxide, lithium molybdate, antimony oxide, lithium antimonate, sodium hydroxide, sodium carbonate, sodium chloride, sodium fluoride, sodium oxide, potassium hydroxide, potassium carbonate, potassium chloride, potassium oxide, calcium hydroxide, calcium carbonate, calcium oxide, calcium chloride, calcium fluoride and ammonium chloride.
[0119] In some embodiments, the sintering temperature during the first sintering process is 700°C-900°C; for example, it can be 750°C-900°C, 750°C-850°C, 750°C-800°C, or 800°C-850°C, etc., without limitation. As an example, the sintering temperature during the first sintering process can be, but is not limited to, 700°C, 720°C, 750°C, 780°C, 800°C, 830°C, 850°C, 870°C, 900°C, or a range between any two of the foregoing values.
[0120] In some embodiments, the sintering time during the first sintering process is 10 hours to 12 hours; for example, it can be 10.5 hours to 12 hours, 11 hours to 12 hours, or 11.5 hours to 12 hours, etc., without specific limitation. As an example, the sintering time during the first sintering process can be, but is not limited to, 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, or a range between any two of the above values.
[0121] In some embodiments, the sintering atmosphere during the first sintering process is selected from one of air and oxygen.
[0122] In some embodiments, the sintering temperature during the second sintering process is 300°C-650°C; for example, it can be 350°C-650°C, 400°C-600°C, 450°C-550°C, or 500°C-550°C, etc., without limitation. As an example, the sintering temperature during the second sintering process can be, but is not limited to, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, or a range between any two of the foregoing values.
[0123] In some embodiments, the sintering time during the second sintering treatment is 3 hours to 10 hours; for example, it can be 3 hours to 9 hours, 4 hours to 8 hours, 5 hours to 7 hours, or 5 hours to 6 hours, etc., without limitation. As an example, the sintering time during the second sintering treatment can be, but is not limited to, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, or a range between any two of the above values.
[0124] In some embodiments, the sintering atmosphere during the second sintering process is selected from one of air and oxygen.
[0125] As a possible embodiment, the method for preparing the positive electrode active material further includes the following steps:
[0126] After preparing a first coating layer on the surface of the inner core, the first coating layer is mixed with a precursor containing aluminum and a precursor containing boron, and subjected to a third sintering treatment to coat the outer surface of the first coating layer with a second coating layer.
[0127] It should be noted that the third sintering treatment is used for descriptive purposes only and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0128] In some embodiments, the precursor containing aluminum element includes one or more of aluminum oxide, aluminum hydroxide, aluminum sulfate, aluminum chloride and aluminum nitrate;
[0129] The precursor containing the boron element includes one or more of boron chloride, boron sulfate, boron nitrate, boron nitride, boron oxide, boron fluoride, boron bromide, boron iodide, boric acid, H2BO5PC5H6B(OH)2, C3H9B3O6, (C2H5O)3B and (C3H7O)3B.
[0130] In some embodiments, the sintering temperature during the third sintering process is 200°C-500°C; for example, it can be 250°C-500°C, 300°C-450°C, or 350°C-400°C, etc., without limitation. As an example, the sintering temperature during the third sintering process can be, but is not limited to, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, or a range between any two of the foregoing values.
[0131] In some embodiments, the sintering time during the third sintering treatment is 5 hours to 15 hours; for example, it can be 6 hours to 14 hours, 7 hours to 13 hours, 8 hours to 12 hours, 9 hours to 11 hours, or 10 hours to 11 hours, etc., without limitation. As an example, the sintering time during the third sintering treatment can be, but is not limited to, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, or a range between any two of the above values.
[0132] In some embodiments, the sintering atmosphere during the third sintering process is selected from one of air and oxygen.
[0133] As an example, the positive electrode active material of the first aspect of the present application can be prepared by the following method:
[0134] Step S1: lithium salt, nickel-containing material precursor and additives are placed in a plow mixer, high-speed mixer or inclined mixer for mixing, and the mixed materials are placed in a kiln for the first sintering treatment. The sintering temperature is 700-900 ° C, the sintering time is 10-20 hours, and the sintering atmosphere is air or high-purity oxygen. The intermediate product after the first sintering is obtained, and the intermediate product is mechanically ground and vibrated to obtain a core; wherein the nickel element, cobalt element, manganese element contained in the nickel-containing material precursor and the M element and M contained in the additive are / The ratio of the sum of the molar amounts of the elements to the molar amount of lithium contained in the lithium salt is 1:(0.9-1.1);
[0135] Step S2: The core, the cerium-containing precursor, the cobalt-containing precursor, and the fluorine-containing precursor are mixed and placed in a coulter mixer, a high-speed mixer, or an inclined mixer. The mixture is mixed in an inert atmosphere or air. The mixture is placed in a kiln for a second sintering treatment at a temperature of 300 to 650° C. for 3 to 10 hours in an air or high-purity oxygen atmosphere. After sintering, a first coating layer is formed on the surface of the core.
[0136] Step S3: After mechanically grinding and vibrating the material obtained in step S2, it is mixed with an aluminum-containing precursor and a boron-containing precursor, and subjected to a third sintering treatment. The sintering temperature is 200-500°C, the sintering time is 5-15 hours, and the sintering atmosphere is air or high-purity oxygen. After the sintering is completed, a second coating layer is formed on the surface of the first coating layer to obtain the positive electrode active material.
[0137] The positive electrode active material prepared by the preparation method of the positive electrode active material according to the second aspect of the present application has a volume particle size distribution diameter ≥ 0.5, a residual lithium content of 0.15wt%-0.35wt%, an oxygen deficiency index ≥ 1.75, and a first coating layer uniformly coated on the outer surface of the inner core formed by cerium element or cerium element and at least one of cobalt element and fluorine element, and a second coating layer uniformly coated on the outer surface of the first coating layer formed by at least one of aluminum element and boron element. The positive electrode active material formed by the above coating has a high gram capacity and rate performance, as well as excellent high temperature cycle performance and high temperature storage performance.
[0138] The third aspect of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, the positive electrode active material layer comprising the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared by the method of the second aspect of the present application.
[0139] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is provided on either or both of the two facing surfaces of the positive electrode current collector.
[0140] In some embodiments, the positive electrode active material may further include lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide, and one or more compounds obtained by adding other transition metal elements or non-transition metal elements to the above lithium-containing compounds.
[0141] As an example, lithium cobalt oxide may include but is not limited to LiCoO 2 ; lithium manganese oxide may include but is not limited to one or more of LiMnO 2 and LiMn 2 O 4 .
[0142] In some embodiments, the positive electrode active material may also include other positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may also include at least one of the following materials: a lithium-containing phosphate with an olivine structure. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, and a composite material of lithium manganese iron phosphate and carbon. The weight ratio of the positive electrode active material in the positive electrode active material layer is 80-100 weight %, based on the total weight of the positive electrode active material layer.
[0143] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc. The polymer material substrate includes but is not limited to one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0144] In some embodiments, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode active material layer is 0-20 weight%, based on the total weight of the positive electrode active material layer.
[0145] In some embodiments, the positive electrode active material layer may further optionally include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode active material layer is 0-20% by weight, based on the total weight of the positive electrode active material layer.
[0146] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40-80 wt % and a viscosity at room temperature adjusted to 5000-25000 mPa·s, the positive electrode slurry is coated on both sides of the positive electrode current collector, and after drying, the positive electrode sheet is formed by cold rolling; the positive electrode powder is coated on one side with a unit area density of 15-45 mg / cm 2 The compaction density of the positive electrode is 2-4.3g / cm 3 , optional 2.5-4.3g / cm 3 The calculation formula of the compacted density is
[0147] Compaction density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).
[0148] secondary batteries
[0149] The fourth aspect of the present application provides a secondary battery, comprising the positive electrode sheet of the third aspect of the present application.
[0150] Thus, the obtained secondary battery has high energy density, high first coulombic efficiency and first discharge gram capacity, and excellent high-temperature cycle performance and high-temperature storage performance.
[0151] The secondary battery, battery module, battery pack, and electric device of the present application are described below with reference to the accompanying drawings as appropriate.
[0152] In one embodiment of the present application, a secondary battery is provided.
[0153] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0154] Negative electrode
[0155] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0156] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is provided on either or both of the two facing surfaces of the negative electrode current collector.
[0157] In some embodiments, in some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode film layer is 70-100 weight%, based on the total weight of the negative electrode film layer.
[0158] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver and silver alloys, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.
[0159] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode active material layer is 0-30% by weight, based on the total weight of the negative electrode active material layer.
[0160] In some embodiments, the negative electrode active material layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode active material layer is 0-20% by weight, based on the total weight of the negative electrode active material layer.
[0161] In some embodiments, the negative electrode active material layer may further include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)). The weight ratio of the other additives in the negative electrode active material layer is 0-15% by weight, based on the total weight of the negative electrode active material layer.
[0162] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the negative electrode slurry has a solid content of 30-70 wt% and a viscosity at room temperature adjusted to 2000-10000 mPa·s; the obtained negative electrode slurry is coated on both sides of the negative electrode current collector, and after a drying process, cold pressing, such as with a roller, is performed to obtain the negative electrode sheet. The negative electrode powder is coated on one side with a unit area density of 7-22 mg / cm 2 , the compaction density of the negative electrode is 1.2-2.0g / m 3 .
[0163] electrolytes
[0164] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0165] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.
[0166] In some embodiments, the electrolyte salt may be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte salt is typically 0.5-5 mol / L.
[0167] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).
[0168] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0169] Isolation film
[0170] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0171] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0172] In some embodiments, the isolation film has a thickness of 6-40 μm, and optionally 12-20 μm.
[0173] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0174] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0175] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0176] In some embodiments, the secondary battery is a lithium-ion battery.
[0177] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 1 having a square structure as an example.
[0178] In some embodiments, referring to FIG2 , the outer packaging may include a housing 11 and a cover 13 . The housing 11 may include a bottom plate and side plates connected thereto, the bottom plate and side plates together forming a receiving cavity. The housing 11 may have an opening communicating with the receiving cavity, and the cover 13 may be positioned over the opening to seal the receiving cavity.
[0179] The positive electrode sheet, negative electrode sheet, and separator can be wound or laminated to form an electrode assembly 12. The electrode assembly 12 is enclosed in the housing. The positive electrode electrolyte is infiltrated between the positive electrode sheet and the separator, while the negative electrode electrolyte is infiltrated between the negative electrode sheet and the separator. The secondary battery 1 can contain one or more electrode assemblies 12, which can be adjusted based on demand.
[0180] In some embodiments, secondary batteries can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0181] In a battery module, multiple secondary batteries can be arranged in sequence along the length of the battery module. Of course, they can also be arranged in any other manner. Furthermore, the multiple secondary batteries can be fixed by fasteners.
[0182] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of secondary batteries are accommodated in the accommodation space.
[0183] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0184] A battery pack may include a battery box and multiple battery modules disposed within the box. The battery box comprises an upper case and a lower case. The upper case can be placed over the lower case to form an enclosed space for accommodating the battery modules. The multiple battery modules can be arranged in any manner within the battery box.
[0185] Electrical devices
[0186] The present application also provides an electrical device comprising at least one of the aforementioned secondary battery, battery module, or battery pack. The secondary battery, battery module, or battery pack can be used as a power source for the device or as an energy storage unit for the device. The device may be, but is not limited to, a mobile device, an electric vehicle, an electric train, a ship, a satellite, an energy storage system, etc.; wherein the mobile device may include, but is not limited to, at least one of a mobile phone and a laptop computer; and the electric vehicle may include, but is not limited to, at least one of a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.
[0187] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0188] Figure 3 shows an example of an electric device 2. The electric device 2 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module can be used.
[0189] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0190] The beneficial effects of the present application are further illustrated below with reference to the examples.
[0191] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application. The materials used in the embodiments and comparative examples of the present application can all be obtained commercially.
[0192] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. All reagents or instruments used without specifying the manufacturer are commercially available conventional products.
[0193] 1. Preparation of positive electrode active materials
[0194] Example 1
[0195] Lithium hydroxide (as lithium salt), Ni 0.92 Co 0.07 Mn0.01 (OH)2 (as a nickel-containing material precursor) and yttrium oxide (as an additive) are mixed in a high-pressure mixer at a molar ratio of lithium to Me of 1.03, and then the mixture is placed in a kiln for the first sintering treatment at a sintering temperature of 760°C, a sintering time of 20 hours, and an O2 atmosphere. After sintering, the mixture is cooled in the furnace to obtain an intermediate product, which is then mechanically ground and vibrated to obtain a core; wherein Me is the sum of nickel, cobalt, manganese and yttrium, and the mass of yttrium in the obtained core relative to the mass content of the core is 1500ppm; the chemical formula of the core is LiNi 0.92 Co 0.07 Mn 0.008 Y 0.002 O2;
[0196] The core and nano-cobalt tetroxide (as a precursor containing the cobalt element), cerium oxide (as a precursor containing the cerium element), and ammonium fluoride (as a precursor containing the fluorine element) are placed in a high-speed mixer for mixing, and then the mixture is placed in a kiln for a second sintering treatment at a sintering temperature of 650° C., a sintering time of 5 hours, and an O2 atmosphere. After sintering, the mixture is cooled in the kiln to form a first coating layer on the surface of the core, and the core is demagnetized and vibrated for standby use. The molar ratio of the cobalt element in the nano-cobalt tetroxide to the cerium element in the cerium oxide is 0.1, and the total mass content of the cobalt element in the nano-cobalt tetroxide, the cerium element in the cerium oxide, and the fluorine element in the ammonium fluoride relative to the mass content of the core is 1000 ppm.
[0197] The inner core after the first coating layer is formed on the outer surface, alumina (as a precursor containing aluminum element), and orthoboric acid (a precursor containing boron element) are placed in a high-speed mixer for mixing, and then the mixture is placed in a kiln for a third sintering treatment at a sintering temperature of 400°C, a sintering time of 5 hours, and an O2 atmosphere. After the sintering is completed, a second coating layer is formed on the surface of the first coating layer to obtain a positive electrode active material; wherein, the mass ratio of aluminum element in alumina and boron element in orthoboric acid is 1:1, and the total mass content of aluminum element in alumina and boron element in orthoboric acid relative to the mass content of the inner core is 1000ppm.
[0198] Example 2-30
[0199] The preparation method of the positive electrode active material in Examples 2-30 is basically similar to the preparation method of the positive electrode material in Example 1, with the main differences being: the type and / or amount of lithium salt, the type and / or amount of nickel-containing material precursor, the type and / or amount of additives, the type and / or amount of cobalt-containing precursor, the type and / or amount of cerium-containing precursor, the type and / or amount of aluminum-containing precursor, the type and / or amount of boron-containing precursor, the temperature and / or time and / or atmosphere in the first sintering treatment, the temperature and / or time and / or atmosphere in the second sintering treatment, and at least one of the temperature and / or time and / or atmosphere in the third sintering treatment.
[0200] It should be noted that, during the preparation process, after the type and / or amount of lithium salt, the type and / or amount of nickel-containing material precursor, the type and / or amount of additive, the type and / or amount of cobalt-containing precursor, the type and / or amount of cerium-containing precursor, the type and / or amount of aluminum-containing precursor, and the type and / or amount of boron-containing precursor are set, the chemical formula of the core in the subsequently prepared positive electrode active material, the mass content of the sum of the mass of cerium element and the mass of cobalt element in the first coating layer relative to the mass content of the core, the molar ratio of cobalt element and cerium element, the mass content of fluorine element relative to the mass content of the core, the mass ratio of aluminum element and boron element in the second coating layer, the mass content of aluminum element relative to the mass content of the core, the mass content of boron element relative to the mass content of the core, and the total thickness of the first coating layer and the second coating layer can be uniquely determined, and the amounts of lithium salt, nickel-containing material precursor, additive, cobalt-containing precursor, cerium-containing precursor, aluminum-containing precursor, and boron-containing precursor can be reversely inferred from the above items.
[0201] For the convenience of description, the above items were measured for the positive electrode active materials prepared in each embodiment. The above items measured are listed in detail in the subsequent Table 1, and the amounts of lithium salt, nickel-containing material precursor, additives, cobalt-containing precursor, cerium-containing precursor, aluminum-containing precursor, and boron-containing precursor used in the preparation process are no longer listed.
[0202] Comparative Example 1
[0203] The difference between the preparation method of the positive electrode active material in Comparative Example 1 and the preparation method of the positive electrode active material in Example 1 is that only the inner core is prepared as the positive electrode active material, and no coating layer is prepared on the outer surface of the inner core.
[0204] Comparative Example 2
[0205] The difference between the preparation method of the positive electrode active material in Comparative Example 2 and the preparation method of the positive electrode active material in Example 1 is that no cerium element is added when preparing the first coating layer, the same mass of cobalt element is used to replace the cerium element, and no second coating layer is prepared outside the first coating layer.
[0206] Various parameters of the positive electrode active materials prepared in the above embodiments and comparative examples, as well as some parameters in the preparation process are shown in Table 1.
[0207] In Table 1, m1 represents the molar amount of lithium contained in the lithium salt; m2 represents the molar amount of nickel, cobalt, manganese contained in the nickel-containing material precursor, and M and M contained in the additive. / The sum of the molar amounts of the elements, M elements include one or more of Zr, Y, Al, Ti, W, Sr, Ta, Mo, Sb, Nb, Na, K and Ca, M / The elements include one or more of N, F, S and Cl; a1 represents the mass content of the sum of the masses of cerium and cobalt elements in the first coating layer relative to the mass content of the core; n1 represents the molar ratio of cobalt and cerium elements in the first coating layer; a2 represents the mass content of fluorine element in the first coating layer relative to the mass content of the core; a3 represents the mass content of aluminum element in the second coating layer relative to the mass content of the core; a4 represents the mass content of boron element in the second coating layer relative to the mass content of the core; n2 represents the mass ratio of aluminum element to boron element in the second coating layer; L represents the total thickness of the first coating layer and the second coating layer; SPAN represents the volume particle size distribution diameter of the positive electrode active material; Rsd(Li) represents the residual lithium content of the positive electrode active material; ODI represents the oxygen deficiency index of the positive electrode active material.
[0208] It should be noted that the chemical formula of the core mentioned above is determined with reference to the EPA 6010D-2014 standard. Specifically: ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) is used for testing. The sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then returned to the ground state from the excited state. In the above process, energy is released and recorded as different characteristic spectral lines, and elemental quantitative analysis is performed based on the characteristic spectral lines.
[0209] In the first coating layer mentioned above, the sum of the masses of cerium and cobalt elements relative to the mass content of the core, and the molar ratio of cobalt and cerium elements are determined with reference to EPA 6010D-2014 standard. Specifically: ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) is used for testing. The sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then recovered from the excited state to the ground state; in the above process, energy is released and recorded as different characteristic spectral lines. Based on the characteristic spectral lines, elemental trace analysis is performed to determine the form of Co and Ce elements, and the above results are calculated.
[0210] In the first coating layer mentioned above, the mass content of fluorine element relative to the mass content of the core is determined by the following method: qualitative or semi-quantitative analysis is performed using EDS (Energy Dispersive X-ray Spectrometer), that is, the sample surface is bombarded with an electron beam in a vacuum chamber to excite the substance to emit characteristic x-rays, and the fluorine element is qualitatively and semi-quantitatively analyzed based on the wavelength of the characteristic x-rays.
[0211] In the second coating layer mentioned above, the mass content of aluminum element relative to the mass content of the core, the mass content of boron element relative to the mass content in the core, and the mass ratio of aluminum element to boron element are measured with reference to EPA 6010D-2014 standard. Specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) is used for testing. The sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then recovered to the ground state from the excited state; energy is released in the above process and recorded as different characteristic spectral lines, and quantitative element analysis is performed based on the characteristic spectral lines.
[0212] The sum of the thicknesses of the first and second coating layers mentioned above was measured using the following method: a sample preparation glue and composite cathode material powder were mixed evenly and then coated onto copper foil to prepare a sample, with the powder weight being five times that of the sample preparation glue. The sample was then dried at 60°C for 30 minutes. The prepared sample was cut into 6mm x 6mm pieces using scissors, secured to a sample stage, and placed in an IB-19500CP ion polisher. The sample edge was aligned parallel to the centerline (X-axis) and positioned 40-60μm along the Y-axis for cutting. After cutting, an X-Max energy dispersive spectrometer (EDS) combined with a Sigma-02-33 scanning electron microscope (SEM) was used to select a suitable particle section on the cut sample, and a linear scan of the characteristic element content of the first coating layer and the characteristic element of the second coating layer was performed along the diameter direction of the particle. The radius of the measured particle was R, the distance from the site where the element content of the first coating layer began to increase compared with the particle core to the center position of the particle was L1, and the distance from the site where the element content of the second coating layer began to increase compared with the particle core to the center position of the particle was L2. The total thickness L of the first coating and the second coating layer was (R-L1) μm.
[0213] The volume particle size distribution of the positive electrode active material mentioned above is measured by the following method: the volume average particle size Dv90, volume average particle size Dv50 and volume average particle size Dv10 of the positive electrode active material are measured by the Mastersizer 3000E laser particle size analyzer of Malvern Instruments Ltd., UK, according to the particle size distribution laser diffraction method of GB / T 19077-2016 / ISO 13320:2009, and then the volume average particle size Dv90, volume average particle size Dv50 and volume average particle size Dv10 of the positive electrode active material are measured based on the formula (d 90 -d 10 ) / d 50 Calculate the volume particle size distribution of the positive electrode active material.
[0214] The residual lithium content of the positive electrode active material mentioned above is determined with reference to GB / T 9736-2008 General method for determination of acidity and alkalinity of chemical reagents. Specifically, 10g-30g of the sample powder to be tested is weighed, 100mL of pure water is added, and the mixture is stirred for 30 minutes. After standing for 10 minutes, a certain amount of filtrate is removed after filtration. A 0.05mol / L hydrochloric acid standard solution is selected and the bubbles in the burette are drained. The corresponding sensor and program are selected to start the potentiometric titration test. The residual lithium content is calculated based on the reaction potential of carbonate and hydroxide.
[0215] The oxygen deficiency index of the positive electrode active material mentioned above is determined by the following method: slowly scan the 35-50° interval in the XRD spectrum of the sample to be tested (<2° / min), and process the image according to smoothing and filtering to obtain the diffraction peak areas I101 and I012 of the (101) crystal plane and (012) crystal plane, and calculate the oxygen deficiency index by (I101 / I012)^0.5.
[0216] 2. Preparation of Secondary Batteries
[0217] 1. Preparation of positive electrode sheet
[0218] The positive electrode active material was placed in a 5L stirring tank and premixed for 30 minutes, and then acetylene black (SP, as a conductive agent) and polyvinylidene fluoride (PVDF, as a binder) were added for secondary dry mixing for 30 minutes. Finally, N-methylpyrrolidone (NMP, as a solvent) was added and rapidly stirred under vacuum conditions to form a slurry. Among them, the mass ratio of positive electrode active material: acetylene black: polyvinylidene fluoride = 96:2:2, and the solid content of the slurry is 70wt%. The slurry was evenly coated on both sides of an aluminum foil with a thickness of 12μm. The coated electrode was taken out after drying in a 130°C oven for half an hour. Among them, the single-sided loading of the positive electrode active material of the electrode is 21.5mg / cm 2 The positive electrode sheets were taken out and then cold-rolled to obtain the compaction density data.
[0219] 2. Preparation of negative electrode sheet
[0220] Artificial graphite (as negative electrode active material), hard carbon (as negative electrode active material), conductive agent acetylene black (as conductive agent), styrene butadiene rubber (SBR, as binder), and sodium carboxymethyl cellulose (CMC, as thickener) are fully stirred and mixed in a deionized water solvent system in a weight ratio of 90:5:2:2:1, and then coated on both sides of copper foil, dried, and cold pressed to obtain a negative electrode sheet.
[0221] 3. Diaphragm
[0222] A polyethylene porous polymer film is used as the separator.
[0223] 4. Preparation of Electrolyte
[0224] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1:1, and then LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte solution. The concentration of LiPF6 in the electrolyte solution was 1 mol / L.
[0225] 5. Preparation of battery cells
[0226] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative sheets to provide isolation, and then wound to form a bare cell. The bare cell is placed in an outer packaging, injected with the prepared electrolyte, and packaged to form a secondary battery.
[0227] 3. Secondary Battery Performance Test
[0228] 1) 1 / 3C full-charge capacity test
[0229] Under a constant temperature environment of 25℃, let it stand for 5 minutes, discharge at 1 / 3C to 2.8V, let it stand for 5 minutes, charge at 1 / 3C to 4.25V, then charge at constant voltage at 4.25V to a current ≤0.05C, let it stand for 5 minutes, and then discharge at 1 / 3C to 2.8V. The discharge capacity at this time is the initial gram capacity, recorded as D0.
[0230] 2) First Coulombic efficiency test
[0231] At 2.8-4.25V, charge the button battery at 0.1C to 4.3V, then charge at constant voltage at 4.3V to a current ≤ 0.05mA, let it stand for 2 minutes, and the charge capacity at this time is recorded as C0. Then discharge it at 0.1C to 2.8V, and the discharge capacity at this time is the initial gram capacity recorded as D0.
[0232] The first effect is calculated according to D0 / C0*100%.
[0233] 3) High temperature cycle performance
[0234] At 45°C, charge at a constant current of 1C to 4.25V, then charge at a constant voltage of 4.25V until the current drops to 0.05C, and then discharge at a constant current of 1C to 2.8V. This is the first-cycle discharge capacity (Cd1). Repeat this charge and discharge cycle for the 300th cycle, and the discharge capacity after n cycles is recorded as Cdn. Capacity retention = discharge capacity after n cycles (Cdn) / first-cycle discharge capacity (Cd1).
[0235] 4) High temperature storage performance
[0236] The secondary batteries prepared in each of the above examples and comparative examples were each placed at a constant temperature of 25°C for 5 minutes, discharged at 1 / 3C to 2.8V, allowed to rest for 5 minutes, and charged at 1 / 3C to 4.25V. They were then charged at 4.25V at a constant voltage to a current of ≤0.05mA and allowed to rest for 5 minutes. The charge capacity at this point was recorded as C0. The batteries were then discharged at 1 / 3C to 2.8V. The discharge capacity at this point was the initial gram capacity, recorded as D0. The batteries were then charged at a constant current of 0.33C to 4.25V and then at a constant voltage to a current of ≤0.05mA. They were allowed to rest for 5 minutes. The batteries were then placed in a 60°C high-low temperature chamber and allowed to rest for 1 hour until the battery temperature reached the target temperature before being stored. After 15 days, the batteries were removed and the above process was repeated at a constant temperature of 25°C. The capacity Dn (n=0, 1, 2, etc.) was recorded every 15 days. The capacity retention rate after 60 days of storage was calculated as (D4-D0) / D0*100%.
[0237] 5) High temperature storage gas production performance
[0238] A full cell with a 100% state of charge (SOC) is stored at 70°C. The open circuit voltage (OCV) and alternating current internal resistance (IMP) of the cell are measured before, during, and after storage to monitor the SOC, and the volume of the cell is measured. Among them, after every 48 hours of storage, the full cell is taken out, left standing for 1 hour, and then the OCV and IMP are tested. After cooling to room temperature, the volume of the cell is measured by the drainage method. The drainage method is to first measure the gravity F1 of the cell alone with a balance that automatically performs unit conversion using the dial data. Then the cell is completely placed in deionized water (with a known density of 1 g / cm3), and the gravity F2 of the cell at this time is measured. The buoyancy force Ffloat of the cell is F1 - F2. Then, according to Archimedes' principle Ffloat = ρgV_drain, the volume of the cell V = (F1 - F2) / ρg is calculated.
[0239] After each volume test, the cell is charged. It is charged at a constant current of 1C to 4.25V, and then charged at a constant voltage of 4.25V until the current drops to 0.05C. After the charging is completed, it is put back into the furnace for continued testing.
[0240] After 60 days of storage, the volume of the cell is measured, and the increase in the volume of the cell after storage relative to the volume of the cell before storage, that is, the gas generation amount, is calculated.
[0241] The performance test results of the above examples and comparative examples are shown in Table 2.
[0242] Table 2
[0243] As can be seen from the results of Examples 1 - 25 and Comparative Examples 1 - 2 in Table 2, by forming a coating layer containing cerium element on at least a part of the outer surface of the core to prepare the positive electrode active material, and using this positive electrode active material to prepare a secondary battery, the first discharge specific capacity and the first Coulomb efficiency of the secondary battery can be improved, and at the same time, the high-temperature cycle performance and high-temperature storage performance of the secondary battery can be enhanced.
[0244] The difference between Examples 1-7 is that the sum of the masses of cerium and cobalt elements in the first coating layer relative to the mass content of the core is different, the smallest in Example 6 and the largest in Example 7. Compared with the results of Examples 1-5, the high-temperature storage gas production in Example 6 increased significantly, while the high-temperature storage capacity retention rate and the high-temperature cycle capacity retention rate decreased. The technicians analyzed that the reason may be that when the sum of the masses of cerium and cobalt elements in the first coating layer relative to the mass content of the core is too low, it may not be possible to form a dense coating layer on the surface of the core, and thus may not be able to effectively reduce the erosion of the active sites of the core by the electrolyte by-products, resulting in limited improvement in the high-temperature cycle performance and high-temperature storage performance of the secondary battery. Compared with the results of Examples 1-5, the first discharge gram capacity in Example 7 is reduced. The technicians analyzed that the reason may be that when the sum of the masses of cerium and cobalt elements in the first coating layer relative to the mass content of the core is too high, it may cause the elements to form a conductive accumulation on the surface of the core, which may lead to a decrease in gram capacity.
[0245] The difference between Example 1 and Examples 8-11 is that the mass content of fluorine in the first coating layer relative to the core is different, with the smallest content in Example 8 and the largest content in Example 11. Compared with Example 1 and Examples 9-11, the high-temperature storage gas production in Example 8 is higher. Technicians analyzed that this may be because the presence of fluorine in the first coating layer helps resist the hydrogen fluoride produced in the battery during high-temperature storage, protects the core surface from corrosion, and reduces gas production. Compared with Example 1 and Examples 8-10, the first discharge gram capacity in Example 11 is reduced. Technicians analyzed that this may be because when the mass content of fluorine in the first coating layer is higher relative to the core, the higher amount of fluorine may cause the valence state of nickel to increase, which may affect the performance of the gram capacity.
[0246] The difference between Example 1 and Examples 12-14 is that the molar ratio of cobalt and cerium in the first coating layer is different. From the results of Example 1 and Examples 12-14, it can be seen that when the molar ratio of cobalt and cerium in the first coating layer is within (0-0.5):1, the secondary battery can have excellent gram capacity, first coulombic efficiency, high-temperature storage performance and high-temperature cycle performance, as well as lower high-temperature storage gas production.
[0247] The difference between Example 1 and Examples 15-19 is that the mass content of the aluminum element and the boron element in the second coating layer relative to the mass content of the core and the mass ratio of the aluminum element and the boron element are different. From the results of Example 1 and Examples 15-19, it can be seen that when the mass content of the aluminum element and the boron element in the second coating layer relative to the mass content of the core and the mass ratio of the aluminum element and the boron element are within the above-mentioned ranges, the secondary battery has excellent gram capacity, first coulombic efficiency, high-temperature storage performance and high-temperature cycle performance, as well as lower high-temperature storage gas production.
[0248] The difference between Example 1 and Examples 21-22 is that the temperature of the second sintering treatment during the preparation of the first coating layer is different, and the temperature of the second sintering treatment in Example 21 is lower; compared with Example 1 and Example 22, the oxygen defect index of the positive electrode active material in Example 21 is lower, the high-temperature cycle capacity retention rate of the secondary battery is reduced, and the high-temperature storage gas production is increased. Technical personnel analyzed that the reason may be that the more oxygen defects in the structure of the positive electrode active material, the weaker the binding on the transition metal elements and other oxygen in the surrounding coordination environment, and the corresponding loss of active substances such as active lithium and transition metals and oxygen loss is greater, so the high-temperature cycle capacity retention rate is reduced and the high-temperature storage gas production is increased.
[0249] The difference between Example 27 and Example 1 is that in Example 27, the sum of the masses of cerium and cobalt elements in the first coating layer relative to the mass content of the inner core, and the mass content of fluorine element relative to the mass content of the inner core are both too high; compared with Example 1, the first coulombic efficiency and the first discharge gram capacity in Example 27 are both reduced. Technicians analyzed that the reason may be that when the sum of the mass contents of cerium and cobalt elements in the first coating layer, and the mass content of fluorine element are too high, the elements may form conductive accumulation on the surface of the inner core, which may lead to a decrease in gram capacity; at the same time, it may cause the residual lithium content of the positive electrode material to be too low, and then lead to too little active lithium in the positive electrode active material, further affecting the coulombic efficiency and gram capacity of the secondary battery.
[0250] The difference between Example 1 and Examples 28-29 is that when preparing the inner core, the relative molar proportion of the lithium element contained in the lithium salt in the raw material is different, the largest in Example 28 and the smallest in Example 29; compared with Example 1, the residual lithium content of the positive electrode active material in Example 28 is significantly improved, and the high-temperature storage gas production of the secondary battery is increased. Technicians analyzed that the reason may be that when the amount of lithium element added is too large, the residual lithium content of the positive electrode active material increases, which may lead to an increase in the side reaction of the residual lithium with the electrolyte, and an increase in the gas production of the secondary battery. Compared with Example 1, the residual lithium content of the positive electrode active material in Example 29 is reduced, the oxygen defect index is reduced, the first coulombic efficiency, first discharge gram capacity, high temperature cycle capacity retention rate, and high temperature storage capacity retention rate of the secondary battery are significantly reduced, and the high temperature storage gas production is increased. Technical personnel analyzed that the reason may be that when the amount of lithium element added is too small, a lithium-containing rock salt phase may be easily formed in the bulk structure of the positive electrode active material, resulting in a significant decrease in electronic conductivity and loss of active lithium, which may lead to a significant decrease in gram capacity and coulombic efficiency, accompanied by a decrease in high temperature cycle capacity retention rate; at the same time, a large number of lithium vacancy defects may also further aggravate oxygen loss, resulting in a decrease in high temperature storage capacity retention rate and an increase in high temperature storage gas production.
[0251] In Example 30, cerium fluoride is used as a precursor containing cerium and fluorine elements, and the amount of coating material used in the first coating layer and the second coating layer is relatively large. The residual lithium content of the positive electrode active material in Example 30 is reduced, the first coulombic efficiency and the first discharge gram capacity of the secondary battery are significantly reduced, and the gas production during high-temperature storage is significantly reduced. Technical personnel analyzed that the reason may be that the large amount of cerium fluoride and cobalt oxide may cause a large amount of residual lithium on the surface of the inner core to be consumed, resulting in a significant decrease in gram capacity; in addition, the large amount of coating of aluminum oxide and boric acid may greatly enhance the dense protection strength of the inner core, so the gas production during high-temperature storage is significantly reduced.
[0252] The above description is merely a specific embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present application, and such modifications or substitutions should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.
Claims
1. A positive electrode active material, include: A core, the core comprising a lithium-containing nickel-based transition metal oxide; in the lithium-containing nickel-based transition metal oxide, the molar proportion of nickel in the total elements other than lithium and oxygen is 50%-100%; A first coating layer is coated on at least a portion of the outer surface of the core, and the first coating layer includes cerium. 2 . The positive electrode active material according to claim 1 , wherein the first coating layer further comprises one or more of cobalt element and fluorine element.
3. The positive electrode active material according to claim 2, wherein the first coating layer has at least one of the following features: (1) The sum of the mass of the cerium element and the cobalt element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 100 ppm-20000 ppm; optionally 1000 ppm-15000 ppm; Optionally, the molar ratio of the cobalt element to the cerium element is (0-0.5):1; (2) The mass content of the fluorine element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the inner core is 0 ppm-60000 ppm; it can be optionally 300 ppm-60000 ppm; it can further be optionally 3000 ppm-45000 ppm.
4. The positive electrode active material according to any one of claims 1 to 3, wherein the chemical formula of the lithium-containing nickel-based transition metal oxide is LiNi x Co y Mn z M a M / b O 2 , in, The M element includes one or more of Zr, Y, Al, Ti, W, Sr, Ta, Mo, Sb, Nb, Na, K and Ca. / The elements include one or more of N, F, S and Cl, 0.6≤x≤1, x+y+z+a+b=1. 5 . The positive electrode active material according to claim 4 , wherein 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2, and 0≤a≤0.
1.
6. The positive electrode active material according to any one of claims 1 to 5, further comprising a second coating layer coated on at least a portion of the outer surface of the first coating layer, wherein the second coating layer comprises one or more of aluminum and boron.
7. The positive electrode active material according to claim 6, wherein the second coating layer comprises the aluminum element and the boron element in a mass ratio of (0.5-2):1; Optionally, the mass of the aluminum element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the core is 100ppm-3500ppm; further optionally, it is 500ppm-2500ppm; Optionally, the mass of the boron element relative to the mass content of the lithium-containing nickel-based transition metal oxide in the inner core is 100ppm-2500ppm; further optionally, it is 500ppm-2000ppm. 8 . The positive electrode active material according to claim 6 , wherein the sum of the thicknesses of the first coating layer and the second coating layer is 0.01 μm to 1 μm.
9. The positive electrode active material according to any one of claims 1 to 8, wherein the volume average particle size Dv90 of the positive electrode active material is denoted as d 90 The volume average particle size Dv50 of the positive electrode active material is denoted as d 50 The volume average particle size Dv10 of the positive electrode active material is denoted as d 10 The volume average particle size Dv90, volume average particle size Dv50 and volume average particle size Dv10 of the positive electrode active material satisfy: (d 90 -d 10 ) / d 50 ≥0.5; optional (d 90 -d 10 ) / d 50 ≥1.
2.
10. The positive electrode active material according to any one of claims 1 to 9, wherein the residual lithium content of the positive electrode active material is recorded as Rsd(Li), and the residual lithium content of the positive electrode active material satisfies: 0.15wt%≤Rsd(Li)≤0.35wt%; optionally 0.18wt%≤Rsd(Li)≤0.24wt%.
11. The positive electrode active material according to any one of claims 1 to 10, wherein the oxygen deficiency index of the positive electrode active material is marked as ODI, and the oxygen deficiency index of the positive electrode active material satisfies: ODI ≥ 1.75; optionally ODI ≥ 1.
8.
12. A method for preparing a positive electrode active material according to any one of claims 1 to 11, comprising the following steps: Mixing a lithium salt, a nickel-containing material precursor and optional additives, and performing a first sintering treatment to prepare the core; The core, a precursor containing cerium, an optional precursor containing cobalt, and an optional precursor containing fluorine are mixed, and a second sintering treatment is performed to prepare the first coating layer on the outer surface of the core; in, The optional additives contain elements including M elements and M / One or more of the elements; the M element includes one or more of Zr, Y, Al, Ti, W, Sr, Ta, Mo, Sb, Nb, Na, K and Ca, the M / The element includes one or more of N, F, S and Cl.
13. The method for preparing a positive electrode active material according to claim 12, wherein the molar amount of the lithium element contained in the lithium salt is recorded as m1, the molar amount of the nickel element, the cobalt element, the manganese element contained in the nickel-containing material precursor, and the M element and M contained in the optional additive are recorded as m2. / The sum of the molar amounts of the elements is recorded as m2, and the ratio of m1 to m2 is (0.9-1.1):
1.
14. The method for preparing a positive electrode active material according to any one of claims 12 to 13, wherein the lithium salt comprises one or more of lithium hydroxide, lithium carbonate, lithium acetate, lithium nitrate, lithium oxalate and lithium sulfate; The optional additives include oxides, hydroxides, acids, fluorides, chlorides, sulfates, nitrates, oxalates, acetates, carbonates, lithium salts, ammonium salts, sodium salts of the M element, and / One or more of the ammonium salts of the elements; Optionally, the optional additives include zirconium oxide, zirconium fluoride, zirconium chloride, yttrium oxide, yttrium sulfate, yttrium nitrate, yttrium oxalate, yttrium acetate, yttrium chloride, aluminum oxide, aluminum fluoride, aluminum chloride, lithium aluminate, titanium oxide, lithium titanate, One or more of tungsten oxide, tungstic acid, ammonium tungstate, sodium tungstate, lithium tungstate, strontium oxide, tantalum oxide, niobium oxide, lithium niobate, molybdenum oxide, lithium molybdate, antimony oxide, lithium antimonate, sodium hydroxide, sodium carbonate, sodium chloride, sodium fluoride, sodium oxide, potassium hydroxide, potassium carbonate, potassium chloride, potassium oxide, calcium hydroxide, calcium carbonate, calcium oxide, calcium chloride, calcium fluoride and ammonium chloride; The precursor containing the cerium element includes one or more of cerium oxide, cerium fluoride, cerium chloride, cerium sulfide, cerium nitrate and cerium hydroxide; The optional fluorine-containing element precursor includes one or more of cerium fluoride and ammonium fluoride; The optional precursor containing the cobalt element includes one or more of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt oxyhydroxide, cobalt acetate, cobalt oxalate and cobalt carbonate.
15. The method for preparing a positive electrode active material according to any one of claims 12 to 14, wherein the first sintering treatment comprises at least one of the following conditions: (1) The sintering temperature is 700℃-900℃; (2) Sintering time is 10h-20h; (3) The sintering atmosphere is selected from one of air and oxygen; The second sintering process includes at least one of the following conditions: (1) The sintering temperature is 300℃-650℃; (2) Sintering time is 3h-10h; (3) The sintering atmosphere is selected from one of air and oxygen.
16. The method for preparing a positive electrode active material according to any one of claims 12 to 15, further comprising the following steps: After the first coating layer is prepared on the surface of the core, it is mixed with a precursor containing aluminum elements and a precursor containing boron elements, and a third sintering treatment is performed to coat the outer surface of the first coating layer with the second coating layer.
17. The method for preparing a positive electrode active material according to claim 16, wherein the precursor containing aluminum element comprises one or more of aluminum oxide, aluminum hydroxide, aluminum sulfate, aluminum chloride and aluminum nitrate; The boron-containing precursor includes boron chloride, boron sulfate, boron nitrate, boron nitride, boron oxide, boron fluoride, boron bromide, boron iodide, boric acid, H 2 BO 5 PC 5 H 6 B(OH) 2 , C 3 H 9 B 3 O 6 , (C 2 H 5 O) 3 B and (C 3 H 7 O) 3 One or more of B.
18. The method for preparing a positive electrode active material according to any one of claims 16 to 17, wherein the third sintering treatment comprises at least one of the following conditions: (1) The sintering temperature is 200℃-500℃; (2) Sintering time is 5h-15h; (3) The sintering atmosphere is selected from one of air and oxygen.
19. A positive electrode sheet, include: Positive electrode current collector; A positive electrode active material layer is located on at least one side of the positive electrode current collector, and the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 11 or the positive electrode active material prepared by the method according to any one of claims 12 to 18.
20. A secondary battery comprising the positive electrode sheet according to claim 19.
21. An electric device comprising the secondary battery according to claim 20.